Contribution of the canonical Wnt pathway in Tribolium anterior-posterior axis patterning - Fu, Jinping (Kansas State University, 2014)
How animals polarize and establish the main axis during embryogenesis has been one of the most attractive questions in Biology. Increasing body of work in various model organisms implicates that most metazoans utilize the canonical Wnt signaling pathway to pattern the anterior-posterior (AP) axis, despite the limited evidence from arthropods. In Drosophila, a highly derived insect, canonical Wnt activity is not required for global AP patterning, but in typical insects including Tribolium castaneum, loss of canonical Wnt activity results in posterior truncation. To determine the eff ects of increased canonical Wnt levels, I analyzed the function of axin, encoding a highly conserved negative regulator of the pathway. Tc-axin transcripts are maternally localized to the anterior pole in freshly laid eggs. Parental RNAi for Tc-axin produced progeny phenotypes that ranged from mildly a ffected embryos with cuticles displaying a graded loss of anterior structures, to severely a ffected embryos lacking cuticles and condensing to the posterior pole of the egg without any de finable structures. Altered expression patterns of several blastodermal markers indicated anterior expansion of posterior fates. Epistasis analysis of other canonical Wnt pathway components and the expansion of Tc-caudal expression, a Wnt target, suggest that the eff ects of Tc-axin depletion are mediated through this pathway and that canonical Wnt activity must be repressed for proper anterior development in Tribolium. These studies provide unique evidence that canonical Wnt activity must be carefully regulated along the AP axis in an arthropod, and support an ancestral role for Wnt signaling in de fining AP polarity and patterning in metazoan development. Additionally, as an anterior structure, the extraembryonic serosa is reduced in Tc-axin RNAi progeny. However, in Tc-pangolin (Tc-pan, a homolog of Wnt downstream component) RNAi progeny, an interesting phenotype was produced that serosa was not only reduced but also separated into distinct anterior and dorsal domains. I carefully recorded this phenomenon with live imaging using a Tribolium transgenic line that expresses GFP in each nucleus. Through careful examination with embryonic fate-map markers, I found that the tissue between separated serosa domains is dorsally extended head lobe. And I also found that in severe phenotype, dorsal serosa was completely gone while anterior serosa not, suggesting independent regulation mechanisms for anterior and dorsal serosa formation. This descriptive data will complement future study in the genetic mechanism underlying serosa formation by providing more details in morphogenesis.
Keywords: Tribolium; Wnt; Axin; Anterior-Posterior axis; Serosa; Evolution and Development (0412); Genetics (0369); Molecular Biology (0307)